Mission Statement Practice: Cascading Impact on Firm Performance - Ismail, Abd. Isa (2003)
Gaps in the existing literature especially in respect of mission statement contributions to firm performance and the consistency that mission statements have been reported to be amongst the most popularly used management tool the world over provide the rationales to the current study. It is a cross-sectional of the descriptive and hypothesis testing types covering four broad areas namely establishment and description of the prevalence of mission practice among Malaysian companies; reasons for the failure of some companies to develop their mission statements; testing and establishing certain hypothesized relationships among mission, decision and performance related variables; and modeling the impact of mission statements on firm performance. A research framework was developed and eleven hypotheses were posited and tested. Primary data was collected from the CEOs or their designated representatives using mailed questionnaire while secondary data was sourced from the companies’ published annual reports. 74 of the 500 KLSE-listed companies randomly sampled and invited to participate responded giving a participation rate of about 15% or a representative rate of slightly more than 11 % of the population. Three types of statistical analysis were utilized namely descriptive, simple linear regression and structural equation modeling with AMOS. The following results were obtained:(i) almost 84% of companies had their written mission statements and the majority (about 53%) were from the production sector; (ii) Companies that failed to develop mission statements attributed their failure not to one but to a host of factors of varying importance; (iii) mission rationale was found to positively influence mission ends and mission means; (iv) mission rationale was observed to exert relatively greater impact on mission means than on mission ends; (v) mission content (ends and means) was observed to positively influence management commitment to the mission; (vi) management commitment to the mission was established to positively influence organization DFP; (vii) organization DFP was observed to positively influence the comprehensiveness of SDP; (viii) comprehensive SDP was found to positively impact firm performance in stable, unstable and irrespective of industrial conditions respectively; and (ix) the impact path of mission statement-firm performance relationship was established through the intermediary sequence of DFP and SDP respectively. Limitations to the current findings were also discussed and directions for future research proposed.